2010
DOI: 10.1348/026151009x424088
|View full text |Cite
|
Sign up to set email alerts
|

Do children with autism use inner speech and visuospatial resources for the service of executive control? Evidence from suppression in dual tasks

Abstract: Three experiments used dual-task suppression methodology to study the use of inner speech and visuospatial resources for mediating central executive performance by children with autism (CWA) and group-matched typically developing (TD) controls. Expt 1 revealed that CWA did not recruit inner speech to facilitate arithmetic task-switching performance: there was no effect of articulatory suppression (AS) on completion time for CWA compared to the TD group. Expt 2 revealed that suppression of visuospatial resource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 53 publications
2
45
0
1
Order By: Relevance
“…For example, as in adults (Chenoweth & Hayes, 2003) inner speech may play a role in the conversion of ideas to a linguistic form, including the processes of lexical selection or formation of syntactic structure (see also McCutchen et al , 1994), or may be implicated in the storage or rehearsal processes to retain these representations whilst the process of handwriting is accomplished. Alternatively, it is possible that inner speech may be used to control the complex procedure of managing and coordinating the constituent processes of writing (Hayes, 1996; Hayes & Flower, 1987; Kellogg, 1996; McCutchen, 1996; Ransdell & Levy, 1996) in a manner similar to that proposed for other cognitively complex tasks (Emerson & Miyake, 2003; Fernyhough & Fradley, 2005; Holland & Low, 2010; Whitehouse et al , 2006). In order to explore these accounts, experimental studies would need to be designed that allow for an interpretation of causality beyond the evidence of correspondence available in the present data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, as in adults (Chenoweth & Hayes, 2003) inner speech may play a role in the conversion of ideas to a linguistic form, including the processes of lexical selection or formation of syntactic structure (see also McCutchen et al , 1994), or may be implicated in the storage or rehearsal processes to retain these representations whilst the process of handwriting is accomplished. Alternatively, it is possible that inner speech may be used to control the complex procedure of managing and coordinating the constituent processes of writing (Hayes, 1996; Hayes & Flower, 1987; Kellogg, 1996; McCutchen, 1996; Ransdell & Levy, 1996) in a manner similar to that proposed for other cognitively complex tasks (Emerson & Miyake, 2003; Fernyhough & Fradley, 2005; Holland & Low, 2010; Whitehouse et al , 2006). In order to explore these accounts, experimental studies would need to be designed that allow for an interpretation of causality beyond the evidence of correspondence available in the present data.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics related to the development of verbal recoding skills have been examined. Verbal coding in STM as an index of the use of inner speech has been explored in executive function tasks in adults (Emerson & Miyake, 2003), children (Al‐Namlah, Fernyhough, & Meins, 2006; Winsler & Naglieri, 2003), and especially in disordered development (Holland & Low, 2010; Whitehouse, Mayberry, & Durkin, 2006; Williams et al , 2008), and also in children's developing literacy skills. Within a typically developing population of children aged 5–8, the size of the PSE was found to make a significant contribution to individual differences in both single‐word reading and text reading and spelling skills (Palmer, 2000b).…”
Section: Introductionmentioning
confidence: 99%
“…However, a comparison of sample characteristics across the relevant studies does not suggest a clear pattern, in this respect. Across studies, performance on experimental measures of verbal mediation has been varied, regardless of whether participants had Asperger's syndrome (Wallace et al 2009;Winsler et al 2007), high-functioning autism (Holland and Low 2009;Lidstone et al 2009;Whitehouse et al 2006), mixedability children with autism (i.e., some children with IQ scores over 70, some with IQ scores under 70; Williams et al 2008), or intellectually low-functioning children with autism (Russell et al 1996). As such, it is not clear that diagnosis/intellectual functioning is a critical variable in determining whether or not inner speech is used by individuals with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, individuals who use inner speech to mediate a given task should show a large drop in performance on the task in question when completing it under conditions of articulatory suppression. However, three studies have found that performance of individuals with ASD on executive functioning tasks is not significantly negatively affected by articulatory suppression, suggesting that these individuals may not be relying on inner speech to mediate the tasks (Holland and Low 2009;Wallace et al 2009;Whitehouse et al 2006).…”
mentioning
confidence: 99%
“…On the other hand, verbal and nonverbal communications were the only social items that did not correlate significantly with BRIEF items in our study. Although it has been proposed that inner speech abilities can help EF skills, Holland and Low (49) showed that in ASDs unlike TDs, inner speech played no important role in an arithmetic task-switching executive control test and that these people were dependent on visuo-spatial resources for completing that task. Joseph et al (13) claimed that ASDs use less language skills in EF control.…”
mentioning
confidence: 99%